Antecedents and Consequences of Brand Hate: Phenomenon on Facebook-Based UPS Community - Debrina Ayu Virgoyanti; Rizky Luxianto (Yayasan Riset dan Pengembangan Intelektual, 2023)
This thesis aims to gain knowledge about brand hate towards the global brand, UPS, and further examine the antecedents and their significant consequences as the influence of consumer behaviour responses on the Facebook-based UPS community. This study uses 1,200 comments on UPS's Facebook page and a thematic analysis method with a netnograph approach to analyse the data. This study provides insight into brand hate that occurs in the Facebook-based UPS brand community where negative past experience acts as an antecedent related to product and ideology differences and brand image of employees and CEO as an antecedent related to the company. Negative past experience consists of service failure, poor customer service, system failure, and perceived price unfairness. The emotional dimensions of brand hate felt by UPS consumers also consist of anger, contempt and disgust, fear, disappointment, shame, and dehumanization. In the end, brand hate results in negative word-of-month consequences, brand revenge, brand switching, brand avoidance, and communicate with the brand. Managerial implications and recommendations for future research are also discussed. Thus, the original findings of this work can provide meaningful guidance for companies to reduce the spread of brand hatred among social media-based brand communities.